Diagnostics for the financial markets: computational studies of payment system: Simulator Seminar Proceedings 2009-2011 - Matti Hellqvist; Tatu Laine (Bank of Finland, 2012)
Chapter 1 Matti Hellqvist - Tatu Laine Introduction 9 Chapter 2 Klaus Abbink - Ronald Bosman - Ronald Heijmans - Frans van Winden Disruptions in large value payment systems: An experimental approach 15 Chapter 3 Edward Denbee - Rodney Garratt - Peter Zimmerman Methods for evaluating liquidity provision in real-time gross settlement payment systems 53 Chapter 4 Ronald Heijmans - Richard Heuver Is this bank ill? The diagnosis of doctor TARGET2 77 Chapter 5 Tatu Laine - Tuomas Nummelin - Heli Snellman Combining liquidity usage and interest rates on overnight loans: an oversight indicator 119 Chapter 6 Ronald Heijmans - Richard Heuver - Daniëlle Walraven Monitoring the unsecured interbank money market using TARGET2 data 135 Chapter 7 Luca Arciero Evaluating the impact of shocks to the supply of overnight unsecured money market funds on the TARGET2- Banca d'Italia functioning: a simulation study 169 Chapter 8 Ashwin Clarke - Jennifer Hancock Participant operational disruptions: the impact of system design 193 Chapter 9 Horatiu Lovin Systemically important participants in the ReGIS payment system 219 Chapter 10 Marc Pröpper - Iman van Lelyveld - Ronald Heijmans Network dynamics of TOP payments 235 Chapter 11 Carlos León - Clara Machado - Freddy Cepeda - Miguel Sarmiento Systemic risk in large value payments systems in Colombia: a network topology and payments simulation approach 267 Chapter 12 Horatiu Lovin - Andra Pineta Operational risk in ReGIS - a systemically important payment system 315 Chapter 13 Robert Oleschak - Thomas Nellen Does SIC need a heart pacemaker? 341 Chapter 14 Robert Arculus - Jennifer Hancock - Greg Moran The impact of payment system design on tiering incentives 379 Chapter 15 Martin Diehl - Uwe Schollmeyer Liquidity-saving mechanisms: quantifying the benefits in TARGET2 411 Chapter 16 Biliana Alexandrova-Kabadjova - Francisco Solís-Robleda The Mexican experience in how the settlement of large payments is performed in the presence of high volume of small payments 431
URN:NBN:fi:bof-201408071682
Keywords: 330; Zahlungsverkehr; Clearing; Liquidität; Geldmarkt; Systemrisiko; Trittbrettfahrerverhalten; Simulation; Computational Economics